Bioinspired Multifunctional Hybrid Hydrogel Promotes Wound Healing. (6th June 2018) - Chen, Guopu; Yu, Yunru; Wu, Xiuwen; Wang, Gefei; Ren, Jianan; Zhao, Yuanjin
Abstract: Inspired by the coordinated multiple healing mechanism of the organism, a four‐armed benzaldehyde‐terminated polyethylene glycol and dodecyl‐modified chitosan hybrid hydrogel with vascular endothelial growth factor (VEGF) encapsulation are presented for efficient and versatile wound healing. The hybrid hydrogel is formed through the reversible Schiff base and possesses self‐healing capability. As the dodecyl tails can insert themselves into and be anchored onto the lipid bilayer of the cell membrane, the hybrid hydrogel has outstanding tissue adhesion, blood cell coagulation and hemostasis, anti‐infection, and cell recruitment functions. Moreover, by loading in and controllably releasing VEGF from the hybrid hydrogel, the processes of cell proliferation and tissue remodeling in the wound bed can be significantly improved. Based on an in vivo study of the multifunctional hybrid hydrogel, it is demonstrated that acute tissue injuries such as vessel bleeding and liver bleeding can be repaired immediately because of the outstanding adhesion and hemostasis features of the hydrogel. Moreover, the chronic wound‐healing process of an infectious full‐thickness skin defect model can also be significantly enhanced by promoting angiogenesis, collagen deposition, macrophage polarization, and granulation tissue formation. Thus, this multifunctional hybrid hydrogel is potentially valuable for clinical applications. Abstract : A bioinspired multifunctional hybrid hydrogel with vascular endothelial growth factor encapsulation is developed by simply mixing four‐armed benzaldehyde‐terminated polyethylene glycol and dodecyl‐modified chitosan. This hydrogel is efficient and versatile for healing both acute and chronic wounds based on its outstanding self‐healing, adhesion, hemostasis, anti‐infective, and other wound‐healing promoting capabilities.